Characterization of the edaphic macrofauna in five grassland agroecosystems from Granma province. Richness and abundance - Chávez, Licet; Rodríguez, Idalmis; Benítez, D.; Torres, Verena; Estrada, W.; Herrera, Magalys; Medina, Yolaine; Bruqueta, Diana (Cuban Journal of Agricultural Science, 2020)
The objective of this study was to evaluate the performance of richness and abundance of edaphic macrofauna in five grassland agroecosystems in Granma province. Samplings were carried out twice a year, once during rainy season and once in dry season, in the period between July 2014 and March 2017. The edaphic macrofauna was collected according to the standard methodology proposed by the Tropical Soil Biology and Fertility (TSBF) and by pitfall traps. An amount of 28,030 individuals was captured in the five agroecosystems, in the three years of research, of them 6,423 in monoliths and 21,607 in pitfall traps. The abundance and richness showed variable performance in both climatic periods in all the studied agroecosystems, with the two sampling methods. During dry season of the second year, a superior performance of macrofauna with respect to rainy period was observed. In Estación de Pastos agroecosystem, the greatest abundance and diversity of edaphic macrofauna was found, which confirms the beneficial effect of silvopastoral systems in this group of edaphic biota. It was concluded that, in the studied grassland agroecosystems, edaphic macrofauna had a heterogeneous performance in the evaluated seasons. Keywords: monoliths, soil organisms, pitfall traps